Standard techniques for formalin-fixed paraffin-embedded tissue : a pathologist’s perspective - al-Sabawi, Hadil Basim Dhannun; Rahawi, Asil Muhammad; al-Mahmud, Sivan Sad Fadil (Iraqi journal of veterinary sciences, 2021)
Histopathology considered as an essential keystone to understanding diseases on a cellular level, without examining affected tissues and cells; will lack the accurate diagnosis. The most common protocol that used worldwide for histopathology is termed as formalin fixed paraffin-embedded techniques; this protocol is the oldest protocol and still used, this technique not invented once, but it is started with a simple process of tissue fixation then undergo several successful steps as it's known today. This protocol depends on formalin to induce tissue fixation and preservation simultaneously, followed by a series of steps to facilitate infiltration of hot paraffin wax in the cells to adjust the density of tissue similar to that of paraffin wax to support tissue during sectioning process at few micrometers of thickness. Many protocols have been invented and modified subsequently to increase the accuracy of tissue processing and facilitate their study under light microscopy. Additionally, the formalin-fixed and paraffin-embedded samples can be considered the most durable process till now. In this review, we are trying to view all fundamental aspects of classical tissue processing that was depended since 1850s, starting from tissue examination, sampling, accessory, labelling, fixation, dehydration, clearance, infiltration, and embedding with hot paraffin wax. Additionally, explain the routine sectioning and staining with classical Hari’s hematoxylin and alcoholic eosin staining protocol. علم أمراض النسيج يعتبر حجر الأساس في فهم الأمراض على المستوى الخلوي، و من دون فحص النسيج و الخلايا المصابة فان التشخيص الدقيق لا يمكن الوصول إليه. إن التقنية الأكثر شيوعا حول العالم تعرف بالنسيج المثبت بالفورمالين و المطمور في مشع البارافين، و الذي يعد من أقدم التقنيات الخاصة بالتقطيع النسجي المرضي و التي ما زالت مستخدمة حتى الأن، إذ إن هذه التقنية لم يتم اختراعها كحزمة متكاملة كما هي عليها اليوم، بل بدأت بعملية التثبيت البسيطة للنسيج و التي أجري عليها العديد من التحديثات و التحويرات الناجحة خطوة بخطوة إلى أن تم تقديمها علمياي بالشكل الحالي. إن هذه التقنية تعتمد على الفورمالين كمثبت ووسط حافظ للنسيج بشكل أساسي والتي تتبع لاحقا بخطوات تعمل على تسهيل إدخال شمع البارافين إلى الخلايا من اجل جعل كثافة النسيج مقاربة إلى كثافة الشمع من اجل دعم عملية التقطيع النسجي إلى مايكرونات قليلة السمك. تم تطوير و اختراع العديد من التقنيات الخاصة و التي جرى عليها العديد من التحويرات اللاحقة من أجل زيادة دقة معاملة النسيج و تسهيل دراسته من خلال المجهر الضوئي، إلا أن التقنية المعتمدة على تثبيت النسيج بالفورمالين وطمره بالبرافين تعد من أكثر التقنيات استخداماي و لحد يومنا هذا. في هذه المراجعة، سنحاول استعراض كل الجوانب الأساسية لمعاملة النسيج الروتينية و التي اعتمدت منذ العقد الخامس للقرن التاسع عشر، و التي تبدأ من فحص النسيج، أخذ العينات النسجية، معاملة و ترقيم النسيج، التثبيت، إزالة الماء، الترويق، التحبيل، و الطمر في شمع البارافين الحار، كما سنحاول إيضاح التقطيع النسجي الروتيني، فضلا عن التلوين بالملون الكلاسيكي بتقنية ملون هاريس الهيماتوكسيلين و الايوسين الكحولي